2016
DOI: 10.1007/s10856-016-5769-3
|View full text |Cite
|
Sign up to set email alerts
|

CeF3-ZnO scintillating nanocomposite for self-lighted photodynamic therapy of cancer

Abstract: We report on the synthesis and characterization of a composite nanostructure based on the coupling of cerium fluoride (CeF3) and zinc oxide (ZnO) for applications in self-lighted photodynamic therapy. Self-lighted photodynamic therapy is a novel approach for the treatment of deep cancers by low doses of X-rays. CeF3 is an efficient scintillator: when illuminated by X-rays it emits UV light by fluorescence at 325 nm. In this work, we simulate this effect by exciting directly CeF3 fluorescence by UV radiation. Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Composite nanoparticles based on the CeO 2 or CeF 3 are promising materials for catalytic or biomedical applications. For example, recently CeF 3 /CeO 2 composite nanoparticles were synthesized by different techniques and were proposed as potential material as highly efficient photocatalyst, CeF 3 /ZnO nanoparticles synthesized, and proposed for applications in novel self‐lighted photodynamic therapy . The same application may be supposed for CeF 3 /CeO 2 composite nanoparticles.…”
Section: Sample Notations Average Particle Sizes Treatment Temperatmentioning
confidence: 99%
“…Composite nanoparticles based on the CeO 2 or CeF 3 are promising materials for catalytic or biomedical applications. For example, recently CeF 3 /CeO 2 composite nanoparticles were synthesized by different techniques and were proposed as potential material as highly efficient photocatalyst, CeF 3 /ZnO nanoparticles synthesized, and proposed for applications in novel self‐lighted photodynamic therapy . The same application may be supposed for CeF 3 /CeO 2 composite nanoparticles.…”
Section: Sample Notations Average Particle Sizes Treatment Temperatmentioning
confidence: 99%
“…Recent proofof-concept studies using nanoscintillator-photosensitizer conjugates demonstrated that this combinatory approach has a strong therapeutic potential in vitro and in vivo. [13][14][15][16][17][18][19][20][21][22][23][24] Biomedical applications of nanoscintillators are currently mostly centered on this concept of radioluminescence-induced PDT. However, factors by which nanoscintillators can augment radiotherapy outcomes also include a potential synergism with radiotherapy [25] and the use of nanoscintillators that emit UV-C photons to expand the amount and types of DNA damage induced during radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy can also produce good therapeutic effects for deep tumors [179], and the therapeutic effect depends to some extent on the energy transfer efficiency of the scintillator. The primary choices of scintillators are rare earth materials [180][181][182] with high photon conversion rates and some metallic materials [183], in addition to a few nonmetallic materials [184] and even quantum dots [185].…”
Section: Radiotherapymentioning
confidence: 99%